Managers, Workers, and Authority - Hsieh, Nien-hê (Journal of business ethics, 2007)
In this paper, I examine the case made by Christopher McMahon for managerial democracy. Specifically, I examine the extent to which McMahon’s account is able to address a series of objections against the case for managerial democracy as articulated by Thomas Christiano. Christiano articulates two sets of objections. First, Christiano argues that McMahon does not succeed in ruling out the possibility that managerial authority is best understood as promissory in its basis, in which case there is no presumption in favor of its democratic exercise. Second, Christiano raises a series of objections to the effect that even if we accept McMahon’s account of the nature of managerial authority, the conclusion for the democratic exercise of that authority by workers at the level of individual economic enterprises does not follow. In the end, I argue that McMahon’s account contains the resources to address these objections if one adopts a specific view about the moral limits to relationships that involve the submission of the will on the part of one person to another. Adoption of this view, however, appears to come at the expense of what I take to be the account’s commitment to liberalism. As such, what I understand this paper to reflect more generally is the apparent difficulty for liberals in arguing that there is something inherently morally troubling about capitalist work relations.